2017
DOI: 10.1038/srep42183
|View full text |Cite
|
Sign up to set email alerts
|

Risk profile and HIV testing outcomes of women undergoing community-based testing in San Diego 2008–2014

Abstract: Women comprised 19% of new HIV diagnoses in the United States in 2014, with significant racial and ethnic disparities in infection rates. This cross-sectional analysis of women enrolled in a cohort study compares demographics, risk behaviour, and sexually transmitted infections (STI) in those undergoing HIV testing in San Diego County. Data from the most recent screening visit of women undergoing voluntary HIV screening April 2008 –July 2014 was used. HIV diagnosis, risk behaviour and self-reported STIs were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The demographics of new HIV diagnoses identified through our ED screening program differed slightly from those reported for new HIV diagnoses by the County of San Diego, with a higher proportion of new HIV diagnoses among African-American populations compared to the San Diego County average (13%) 22 . Compared to the Early Test community-based HIV screening program, our ED screening programs identified higher proportions of women, African-Americans, and individuals indicating heterosexual contact as their main risk factor 5,23 . Both community-based HIV screening programs and routine testing in EDs may therefore have a combined effect on reducing HIV transmission and infection in the community.…”
Section: Discussionmentioning
confidence: 91%
“…The demographics of new HIV diagnoses identified through our ED screening program differed slightly from those reported for new HIV diagnoses by the County of San Diego, with a higher proportion of new HIV diagnoses among African-American populations compared to the San Diego County average (13%) 22 . Compared to the Early Test community-based HIV screening program, our ED screening programs identified higher proportions of women, African-Americans, and individuals indicating heterosexual contact as their main risk factor 5,23 . Both community-based HIV screening programs and routine testing in EDs may therefore have a combined effect on reducing HIV transmission and infection in the community.…”
Section: Discussionmentioning
confidence: 91%
“…Other limitations include the single-center design of this study, and that our study sample was mainly white and with a significant proportion of Hispanics, which is representative of the Early Test cohort [22] but may differ from other settings in the United States [13]. In terms of self-identified gender, compared to previous published work with the Early Test cohort from a different time period [36,37,39], our study sample had a slightly smaller proportion of transgender persons and women, and a greater proportion of MSM among male testers, reflecting time trends as well as ongoing preexposure prophylaxis studies specifically targeting women and transgender persons in San Diego. While frequency of symptoms did not differ between men and women who tested negative for HIV, we were not able to compare frequency of symptoms between sex or gender in those with AHI, due to the fact that MSM account for the vast majority of AHI diagnoses with the Early Test in San Diego.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, symptoms may be less subject to stigma, and therefore individuals may be more comfortable disclosing symptoms than sexual behaviors. Another downside to riskbased scores is that, as previously discussed, reported risk factors are not uniform in a population, but differ based on race, sex, gender, and likely other factors [13,36,37]. For example, a recent cross-sectional study by Liu et al [38] assessing risk factors among Chinese migrant worker MSM in Beijing showed that the amount of time spent living in Beijing was independently associated with HIV infection, and migrant MSM were twice as likely to have HIV infection compared to local resident MSM.…”
Section: Discussionmentioning
confidence: 99%